School trip - Craft, Jerry (Quill Tree Books : HarperAlley, 2023)
Jordan, Drew, Liam, and their friends from Riverdale Academy Day School are going on a school trip to Paris, France, and Jordan can't wait to see all the famous artwork in the City of Lights. But when things don't go as planned and the faculty assignments get mixed up, the students find they'll be traveling with different teachers than expected. In addition, Jordan is accepted into art school, and he must decide whether or not he wants to be the new kid once again.